Oral sustained delivery of atenolol from floating matrix tablets - Formulation and in vitro evaluation - Srivastava A.K.; Wadhwa S.; Ridhurkar D.; Mishra B. (My University, 2025)
Floating matrix tablets of atenolol were developed to prolong gastric residence time and increase drug bioavailability. Atenolol was chosen as a model drug because it is poorly absorbed from the lower gastrointestinal tract. The tablets were prepared by direct compression technique, using polymers such as hydroxypropyl methylcellulose (HPMC K15M, K4M), guargum (GG), and sodium carboxymethylcellulose (SCMC), alone or in combination, and other standard excipients. Tablets were evaluated for physical characteristics viz. hardness, swelling index, floating capacity, thickness, and weight variation. Further, tablets were evaluated for in vitro release characteristics for 8 hr. The effect of effervescent on buoyancy and drug release pattern was also studied. In vitro release mechanism was evaluated by linear regression analysis. GG- and SCMC-based matrix tablets showed significantly greater swelling indices compared with other batches. The tablets exhibited controlled and prolonged drug release profiles while floating over the dissolution medium. Copyright © 2005 Taylor & Francis Inc.